Treasure island - Stevenson, robert louis (UK: Oxford university press., 2019)
Treasure Island by Robert Louis Stevenson is a timeless adventure novel centered around a young boy named Jim Hawkins, who embarks on a perilous journey to find a hidden pirate treasure. After discovering a treasure map among the belongings of a deceased pirate, Jim joins forces with Dr. Livesey and Squire Trelawney to organize an expedition to a mysterious island. They set sail aboard the Hispaniola, led by the honorable Captain Smollett. However, their journey is fraught with danger, as many of the crew members, including the charismatic and cunning one-legged cook Long John Silver, are secretly plotting a mutiny to claim the treasure for themselves. As alliances shift and danger lurks at every turn, Jim must navigate treacherous waters, both literal and metaphorical, to survive. Filled with adventure, suspense, and moral complexity, Treasure Island explores themes of loyalty, greed, and bravery, cementing itself as one of the greatest and most influential pirate tales in literature.
Keywords: Fiction story